The Influence of Financial Performance and CSR on Company Value with Earnings Management as a Mediating Variable - Sulistiani, Nadifa Tyas; Ramadhanti, Wita; Setyorini, Christina Tri (Ratio : Reviu Akuntansi Kontemporer Indonesia, 2024)
This research aims to determine financial and CSR performance on firm value with earning management as a mediating variable. This study examined manufacturing companies that were listed on the Indonesia Stock Exchange (BEI) between 2018-2022. The variables in this research include endogenous variables which is company value as measured by Tobin’s Q indicator; exogenous variable which isf financial performance according to the total Asset Turnover Ratio and Return on Assets and CSR as measured by the GRI Standard; and earning management that measured by Modified Jones Model as mediating variable. The research’s population is made up of 195 companies, and samples are selected using a purposive sampling method so there are 16 companies that meet the criteria. The data analysis technique used is SEM PLS with the WarpPLS application. According to the research findings, CSR has a positive and significant impact on earnings management, but financial performance has a negative impact on it. Earnings management has a positive effect on company value. Financial performance has a positive effect on company value, while CSR has a negative effect on company value. The results of the mediation analysis show that earnings management is unable to mediate the influence of company financial performance on company value. However, earnings management mediating the influence of CSR on accepted company value.